Microwave Assisted Synthesis, Solution State, Spectral Studies and Theoretical Treatment of Pd(II) , Pt(IV) and Au(III) ions Complexes Containing 2-Benzamide Benzothiazole (Baghdad Science Journal, 2015)
2-benzamide benzothiazole complexes of Pd(II) , Pt(IV) and Au(III) ions were prepared by microwave assisted radiation. The ligand and the complexes were isolated and characterized in solid state by using FT-IR, UV-Vis spectroscopy, flame atomic absorption, elemental analysis CHNS , magnetic susceptibility measurements , melting points and conductivity measurements. The nature of complexes in liquid state was studied by following the molar ratio method which gave results approximately identical to those obtained from isolated solid state; also, stability constant of the prepared complexes were studied and found that they were stable in molar ratio 1:1.The complexes have a sequar planner geometry except Pt(IV) complex has octahedral . A theoretical treatment of ligand and its metal complexes in gas phase were studied using HyperChem-8 program, moreover, ligand in gas phase also has been studied using Gaussian program(GaussView Currently Available Version (5.0.9) along with Gaussian 09 which was the latest in the Gaussian series of programs).